TaḥSīn al-Idrāk fīī Marḥālāh aṭ-TuFūlāh al-Mubākkirāh min Khilāl Ta`allum al-Lugāh al-‘Arābīīah al-Qā-im `alā al-Ghānī - Salsabila, Dila Fairuz; Barus, Rifki Bunayya (Al Maghazi : Arabic Language in Higher Education, 2024)
This research aims to explore the potential of songs in improving the cognitive abilities of young children, especially in terms of mastering Arabic vocabulary. Using a qualitative approach, this research analyzes children’s responses to learning Arabic through songs. The research results show that songs can stimulate children’s memory, attention and understanding of new vocabulary. Apart from that, songs also create a pleasant learning atmosphere so that children are more motivated to learn Arabic. These findings indicate that song-based Arabic language learning can be an interesting and effective alternative for introducing Arabic to young children and contribute to the development of Arabic language learning methods that are more fun and meaningful for young children.